Eco-digital storytelling: Engaging historically excluded populations in environmental action through mentoring, geospatial technology, and digital media storytelling - Cisneros, Laura; Campbell, Todd; Freidenfelds, Nicole; Lindemann, Anna; Elliot-Famularo, Heather; Chadwick, Cary; Dickson, David; Park, Byung-Yeol (Frontiers in Education, 2023)
The environment, science, technology, engineering, arts, and mathematics fields (a collection of fields we call E-STEAM) continue to grow and remain economically and ecologically important. However, historically excluded groups remain underrepresented in science and technology professions, particularly in environmental and digital media fields. Consequently, building pathways for historically excluded students to enter economically viable and ecologically influential E-STEAM professions is critically important. These new pathways hold promise for increasing innovation within these fields and ensuring a multiplicity of representation as these fields are shaped and reshaped to attend to the plural interests of diverse communities. Consequently, this conceptual paper describes an eco-digital storytelling (EDS) approach to engaging historically excluded populations in science, technology, engineering, and mathematics (STEM). This approach offers structured learning opportunities connected to learner interests and community needs with the aim of increasing E-STEAM identity and career interest of teens from groups historically excluded from E-STEAM fields. E-STEAM identity is a meaning one can attach to oneself or that can be ascribed externally by others as individuals interact and engage in E-STEAM fields in ways that foreground the environment. The EDS approach leverages community-based action, technology and digital media, and arts and storytelling as entry points for engaging learners. EDS is designed to increase teens’ content knowledge within multiple E-STEAM fields and to provide numerous technology-rich experiences in both application of geospatial technologies (i.e., GPS, interactive maps) and digital media creation (i.e., video, animation, ArcGIS StoryMaps) as a way to shape teens’ cultural learning pathways. Examples of rich digital media presentations developed to communicate the EDS approach and local environmental opportunities, challenges, and projects are provided that exemplify how both participation in and communication of environmental action can contribute to more promising and sustainable futures.